Instructional Alignment of PjBL in ECE: An Analysis of Learning Strategies, Methods, and Techniques - Avanti Vera Risti Pramudyani; Diah Ayu Praharani; Hani Irawati; Risanti Dhaniaputri; Tanaya Qotrunada Rutriningtyas; Irma Sukarelawan (LP. Ma'arif Janggan Magetan, 2026)
This study was prompted by the discovery of instructional alignment gaps in the implementation of STEAM-based Project-Based Learning (STEAM-PjBL) in early childhood education (PAUD), particularly with regard to the alignment of objectives, strategies, methods, techniques, learning activities, and assessments. The study aims to analyse instructional alignment in STEAM implementation based on PjBL in PAUD, focusing on the relationship between learning strategies, methods, and techniques. The study used a qualitative approach with a case study design at TK ABA Ngampilan Yogyakarta, with one head teacher and three teachers selected through purposive sampling. Data was collected through observation, semi-structured interviews, and documentation, and analysed using Braun and Clarke's thematic analysis. The results of the study show that the implementation of STEAM-PjBL has demonstrated alignment between the learning objectives, activities, strategies, methods, techniques, and assessments through the active involvement of children in exploration, collaboration, experimentation, and reflection. However, challenges were still found in the form of extrinsic reward dominance, imbalanced participation in group work, insufficient reflective scaffolding, and discrepancies between written plans and the implementation of learning activities. This study emphasises the importance of strengthening teachers' pedagogical competencies in designing inclusive and meaningful STEAM-PjBL learning activities in early childhood education.